Fishes of Southern Japan and the Ryukyus. - Burgess, W. and H.R. Axelrod (Neptune City, New Jersey T.F.H. Publications, 1972)
Pacific marine fishes ; Bk.1
Keywords: Fishes--Ryukyu Islands--Identification.; Fishes--Ryukyu Islands; Marine fishes--Japan--Ryukyu Islands--Identification.; Marine fishes--Japan--Ryukyu Islands